冷战时期的呼唤 ：从新加坡“丽的呼声”的译名看翻译的政治功能 = A voice during the Cold War : the study of Singapore Rediffusion and its political function - 林杨清 Ling, Yang Qing (2013)
新加坡独立前（1965年）的首个华语广播电台Rediffusion在殖民时期扮演者重要的角色。电台于1949年在新加坡开台，到2012年结业之前，以“丽的呼声”这个中文名称备受新加坡人认识和欢迎。然而，从原语来看，Rediffusion一词的意义，并不会翻译出“丽的呼声”的意涵出来。若从语音看来，Rediffusion华文译名,亦不是当时新加坡社会最广泛使用的语言──闽南语──翻译出来。那么，Rediffusion这个名词的翻译，如何造就“丽的呼声”译名的创立？一个外来词通过翻译而被整个社会广泛接受，再成为定译的过程，与当地社会的政治、文化及历史有着不可分割的关系。事实上, 任何翻译都在特定的时空内产生，译语的生产过程，亦必定会反映影响社会的文化生态及意识形态，即使这些意识形态是多么的隐而不显。另一方面，翻译的过程，承载了两种文化交往及冲突的痕迹，一些产生自政治动荡或文化碰撞时期的译名，就更是刻铭了不同文化协商的过程。 本文以Rediffusion作为考察对象，深入讨论这家英国电台于1945年到1991年历史学家定义为“冷战”的时期，如何在东南亚最重要的战略地点——新加坡，设立广播频道的历史过程，并以一个为人称道的译名达到其传播功能。本文以翻译研究中的功能论，以详细的历史文献，深入讨论“丽的呼声”译名的由来，并分析及评鉴译名的种种元素，从而揭示Rediffusion广播媒体背后宣传的政治及意识形态。本文最后会指出，作为冷战时期的重要英国广播媒体，如何通过翻译与翻译语本地化的过程，利用“丽的呼声”的译名，转换“传播再传播”的意义，把冷战时期的西方文化和意识形态传达成为“美丽声音”的过程。 Before Singapore’s independence in 1965, the first Mandarin broadcasting firm― Rediffusion played an important part in contributing to the broadcast history of Singapore. It started out in 1949 and was widely recognized by local listeners until the firm ceased operations in 2012. Since then, it was largely identified by its Chinese name―“丽的呼声”.The new translated name was well-known to the local Chinese, which was its largest audience group. However, it is impossible to relate the meaning of“丽的呼声”to the original meaning of “Rediffusion”. By analysing the phonology of“丽的呼声”, one can conclude that“丽的呼声”does not originate from a Hokkien phonology―which was a widely used dialect in Singapore during the 1940s. This leads us to the question of how the mandarin translation of “丽的呼声”came about. As a foreign word is translated to its targeted language, the process of translation projects an inseparable relationship between the targeted society, culture, politics and history. In fact, given a specific time and space, the translation process and the translated product also reflect the impact of ecology and ideology on the society; even if these ideologies are rather implicit. On the other hand, the process of translation bears traces of conflicts and cultural exchanges between two different societies, which could arise due to periods of political unrest and cultural collision. These are important literary papers that reveal the complicated culture negotiation process. This paper focuses on the study of Singapore’s Rediffusion radio station during the Cold War (1945―1991), and the importance of this British radio station in Singapore, especially where Singapore is an important strategic location in Southeast Asia (SEA). Taking into consideration the importance of SEA during the Cold War, this paper will also examine how the establishment of “Rediffusion” and its translation was able to assist the firm in its dissemination. Using the Functional Theory in translation studies, and combining detailed historical papers, this paper further discusses the origin of the translated word“丽的呼声”, and the various elements involved in the translation process, thereby revealing the political and ideological motive of the British media. Lastly, it rediscovers how the use of the new translated text“丽的呼声”, and the process of translation and translation language localization, could convert the original meaning of “re-dissemination”, into portraying the West as a “beautiful voice”― both culturally and ideologically.